ANALISIS KADAR RESIDU PESTISIDA PADA PANGAN SEGAR DI DINAS PERTANIAN DAN KETAHANAN PANGAN YOGYAKARTA - Listanaya Rizkina; Ibdal Ibdal; Agung Suprihanto (Universitas Teuku Umar, 2021)
Presence of pesticide residues in agricultural products can cause health problems if the products are consumed by human. Some of the agriculture products such as long beans, mustard meatballs, cauli flower, pier, onien and pies are contaminated by the pesticide residues. Four from these produts, long beans, mustard meatballs, cauliflower and pier are common products sold in Karangijo Market, Ponjong, Gunung Kidul Regency. Therefore, this study tries to analyze the level of pesticide residue in four aggriculutre products. Type of this research was conducted by observational survey with a descriptive approach. All samples were randomly collected from the traditional market in Karangijo, Ponjong, Gunung Kidul Regency. Residues of pesticide in all samples were extracted by using a washing solution. Then, the extracted solutions were tested by using the rapid test kit (RTK). All experiments were carried out at at the OKKPD Laboratory at the Department of Agriculture and Food Security Yogyakarta. The results showed that the level of pesticide residues in four agriculture products long beans, mustard meatballs, cauliflower and pier positive low were lower than the required threshold of 0.5 ppm. This fact means that these samples were safe for consumed.